Fat mass and obesity–mediated N6-methyladenosine modification modulates neuroinflammatory responses after traumatic brain injury - Xiangrong Chen; Jinqing Lai; Zhe Wu; Jianlong Chen; Baoya Yang; Chunnuan Chen; Chenyu Ding (Neural Regeneration Research)
The neuroinflammatory response mediated by microglial activation plays an important role in the secondary nerve injury of traumatic brain injury. The post-transcriptional modification of N6-methyladenosine is ubiquitous in the immune response of the central nervous system. The fat mass and obesity-related protein catalyzes the demethylation of N6-methyladenosine modifications on mRNA and is widely expressed in various tissues, participating in the regulation of multiple diseases’ biological processes. However, the role of fat mass and obesity in microglial activation and the subsequent neuroinflammatory response after traumatic brain injury is unclear. In this study, we found that the expression of fat mass and obesity was significantly down-regulated in both lipopolysaccharide-treated BV2 cells and a traumatic brain injury mouse model. After fat mass and obesity interference, BV2 cells exhibited a pro-inflammatory phenotype as shown by the increased proportion of CD11b+/CD86+ cells and the secretion of pro-inflammatory cytokines. Fat mass and obesity-mediated N6-methyladenosine demethylation accelerated the degradation of ADAM17 mRNA, while silencing of fat mass and obesity enhanced the stability of ADAM17 mRNA. Therefore, down-regulation of fat mass and obesity expression leads to the abnormally high expression of ADAM17 in microglia. These results indicate that the activation of microglia and neuroinflammatory response regulated by fat mass and obesity-related N6-methyladenosine modification plays an important role in the pro-inflammatory process of secondary injury following traumatic brain injury.